IMPROVING THE USE OF INFORMATION AND COMMUNICATION TECHNOLOGIES IN TEACHING THE SUBJECT OF FUNCTIONS IN SECONDARY SCHOOLS (World Bulletin of Management and Law, 2022)
This article discusses the advantages of using information technology in the teaching of mathematics and how to increase the visual acuity of the topic through the use of multimedia in teaching the topic of function. One of the main tasks of education today is to enter the modern information society. Information technologies are being actively introduced into the educational process, computer training programs, tests, modeling, presentations are used in the lessons. The computer can be used as a source of educational information, a visual aid, a simulator or a diagnostic and control tool